Introduction of wild berberis species of Kazakhstan and Uzbekistan flora into in vitro culture (Experimental biology, 2016)
The article shows the results on the introduction of 4 barberry species into in vitro culture (B. iliensis, B. sphaerocarpa, B. integerrima and B. oblonga). The seeds of 11 forms of B. iliensis and 7 forms of B. sphaerocarpa were collected from wild populations of Almaty region of Kazakhstan; 22 forms of B. integerrima and 2 forms of B. oblonga were collected in Zarafshan National Park of Uzbekistan. The conditions for seed germination in moist perlite and sterilization of apical shoots in 0,1% HgCl2 solution for 7 minutes were selected allowing to obtain 50% of viable shoots. Testing of the plant material in the in vitro culture for the presence of endophytic infection on specialized medium 523 let to get 100% aseptic material. Established aseptic in vitro collection of barberry consisting of 42 accessions will be used for micropropagation and the creation of a cryogenic bank, as well as for setting up elite nurseries and for the international exchange of genetic resources.
Keywords: Berberis; seeds; in vitro; aseptic collection.